ON THE QUESTION OF THE PRINCIPLES OF THE ORGANIZATION INDIVIDUAL TRAINING IN THE SYSTEM MUSIC TEACHER TRAINING (Pedagogy of Higher and Secondary Education, 2004)
In the article are given modern principles of organization of the individual approach in the system of personal-oriented education of the teaches of music. The author investigates the content of principals of musical and general pedagogic, the ways of their realization in musical-performing preparing of the teacher of music in the secondary school.The author reveals the content of musical-performing preparing of the future teacher of music, which is organized on the basic of principals of professional-oriented education